Lower dementia risk with anticoagulation and ablation in patients with atrial fibrillation - Daehoon Kim; Pil-Sung Yang; Boyoung Joung (International Journal of Arrhythmia, 2021)
Abstract Atrial fibrillation (AF), the most common cardiac arrhythmia in the elderly population, has been associated with an impairment of cognitive function and an increased risk of dementia. Even though there does not appear to be solid evidence that any specific treatment prevents or delays AF-associated cognitive decline, evidence is accumulating regarding the possible treatment strategies for preventing dementia. Oral anticoagulation, especially non-vitamin K antagonist oral anticoagulants rather than warfarin use, has been suggested to be associated with reduced risk of dementia. Successfully maintaining sinus rhythm using catheter ablation might be also helpful in preventing subsequent dementia in patients with AF. In this review, we critically appraise the proposed treatment strategies for preventing AF-associated cognitive decline.